2014
DOI: 10.1186/1477-7819-12-310
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of poorly differentiated clusters in invasive breast cancer

Abstract: BackgroundOur study aimed to assess the prognostic value of poorly differentiated clusters (PDCs) in invasive breast cancer.MethodsA total of 146 cases of operable invasive ductal carcinoma that was not otherwise specified (IDC-NOS), from 2002 to 2009, were pathologically reviewed. Cancer clusters with five or more cancer cells and lacking gland-like structures were counted from a field containing maximum clusters in H & E slides under a × 20 objective lens (0.950 mm2 field of vision).ResultsTumors with <5, 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 29 publications
0
23
1
1
Order By: Relevance
“…Rasheed and colleagues found that poorly differentiated invasive ductal carcinoma have high Her-2/neu positivity [8]. Sun et al found that poorly differentiated clusters in invasive breast cancer is also associated with Her-2/neu overexpression [20]. This outcome cannot be effectively compared with our study in view of the fact that most of the tumours fall into grade II and III.…”
Section: Discussioncontrasting
confidence: 58%
“…Rasheed and colleagues found that poorly differentiated invasive ductal carcinoma have high Her-2/neu positivity [8]. Sun et al found that poorly differentiated clusters in invasive breast cancer is also associated with Her-2/neu overexpression [20]. This outcome cannot be effectively compared with our study in view of the fact that most of the tumours fall into grade II and III.…”
Section: Discussioncontrasting
confidence: 58%
“…While many models suggest metastasis begins with individual cells undergoing the epithelialmesenchymal transition (EMT) and leaving the boundaries of the primary tumor, analysis of tumor-stroma interfaces in clinical samples has revealed that it is the presence of invasive cell clusters [42], also termed tumor buds, that correlates with metastatic progression and poor prognosis in various solid tumor types [43][44][45][46][47]. This highlights the importance of understanding the cellular and molecular underpinnings of collective cancer cell invasion and the need for physiologically relevant in vitro models supporting this crucial mode of invasion.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies have evaluated the prognostic significance of PDC in other carcinoma types, including Crohn's disease-associated small bowel adenocarcinoma, [54][55][56] breast carcinoma and auditory canal carcinoma, with all finding high PDC grade to be significantly associated with adverse clinical outcomes. Interestingly, PDC grade in breast and auditory canal carcinomas was associated with strong interobserver agreement (kappa values 0.74 and 0.89, respectively), similar to that reported for CRC.…”
Section: Significance Of Pdc In Non-cr Cancersmentioning
confidence: 99%